Neonatal Marfan syndrome: a case report of a novel fibrillin 1 mutation, with genotype-phenotype correlation and brief review of the literature - Flaminia Pugnaloni; Domenico Umberto De Rose; Maria Cristina Digilio; Monia Magliozzi; Annabella Braguglia; Laura Valfrè; Alessandra Toscano; Andrea Dotta; Alessandra Di Pede (BMC, 2024)
Abstract Background Neonatal Marfan syndrome (nMFS) is a rare condition characterized by severe phenotype and poor prognosis. nMFS is caused by mutations in a specific region of the fibrillin 1 gene (FBN1). Prompt recognition of typical signs of neonatal presentation, such as characteristic facial anomalies with senile appearance, arthrogryposis, and campto-arachnodactyly, is fundamental for performing an early cardiological examination. This usually reveals rapidly progressive cardiovascular disease due to severe atrioventricular valve dysfunction. Case presentation Herein, we report the case of an early-onset cardiac failure in a neonate with Marfan syndrome, with a brief review of the literature of cases with cardiac involvement in neonatal age. Clinical exome sequencing identified the novel heterozygous de novo missense variant c.3152T > G in FBN1 gene (NM_000138.4), causing the aminoacidic change p.Phe1051Cys. Phenotype-genotype correlation led to a multidisciplinary diagnostic and management workflow. Conclusion The prompt recognition of a typical phenotype such as that of Marfan syndrome should lead to a detailed evaluation and close follow-up of cardiac morphology and function. Indeed, multi-disciplinary evaluation based on genotype-phenotype correlations of nMFS cases is essential to finding out the best medical and surgical approach, predicting the relevant impact on patient prognosis, and adequately counseling their families.